Me and My Secrets: A Phenomenological Study of Communication Privacy Management of Atheists in the Indonesian Context Regarding Their Identity - Azzumar Adhitia Santika; Rudi Sukandar (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
Being an Atheist is always an unpopular choice in the middle of high religious context society. The stigma and pressure from religious groups forced Atheists in Indonesia to hide their identity in public generally and when taking care of the affairs of state administration. This research utilized Communication Privacy Management and Dramaturgy Theory alongside the phenomenology perspective to reveal how Atheists in Indonesia live their